Study rain influence of chemical water quality in Sungai Perlis - Nurul Huda Abdullah (School of Environmental Engineering, University Malaysia Perlis, 2013)
This is because the rain always does the hydrology cycle with the surface water on the earth. Rain water will gather after the process of evaporation and evapotranspiration.